2018
DOI: 10.20396/bjos.v17i0.8652929
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging on bond strength of artificial teeth to denture base acrylic resins

Abstract: Aim: The aim of this study was to evaluate the bond strength of artificial teeth to different types of denture base resins when submitted to thermomechanical cycling (TMC). Methods: Sixty artificial mandibular first molars (Trilux, Vipi) were randomly divided into 3 groups according to denture base acrylic resins (Vipi Wave, Vipi Cril, and Vipi Cril Plus, Vipi). The teeth were fixed onto self-polymerizing acrylic resin bars (0.5 cm2 cross-section x 2 cm height), and the set was included in a metal flask using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Studies have shown that bond strength between acrylic teeth and denture base resins could be affected by aging processes such as thermocycling procedure, which could decrease the overall bond strength. 40 , 41 Baia et al 42 concluded that prolonged bleaching either post- and pre-restoration using 4% hydrogen peroxide decreased tooth bonding. However, in another study, decreased bond strength was found in teeth bonded to CAD/CAM and 3D printed denture base resins, when compared to the heat cured acrylic resin, with no significant influence following aging.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that bond strength between acrylic teeth and denture base resins could be affected by aging processes such as thermocycling procedure, which could decrease the overall bond strength. 40 , 41 Baia et al 42 concluded that prolonged bleaching either post- and pre-restoration using 4% hydrogen peroxide decreased tooth bonding. However, in another study, decreased bond strength was found in teeth bonded to CAD/CAM and 3D printed denture base resins, when compared to the heat cured acrylic resin, with no significant influence following aging.…”
Section: Discussionmentioning
confidence: 99%
“…However, long-term examinations are necessary to fully establish the connection of the denture plate with the teeth. As was shown in the literature, the connection may weaken over time by about 10–15% [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 92%